2002
DOI: 10.1021/ja027444a
|View full text |Cite
|
Sign up to set email alerts
|

The Topochemical 1,6-Polymerization of a Triene

Abstract: The first topochemical 1,6-polymerization of a triene has been observed. The required supramolecular structure for this polymerization was achieved by the pi-pi stacking of the isonicotinate functionality. The crystal environment of this polymerization reaction controlled both the molecular and supramolecular structure of the polymer and allowed its structure to be determined by single-crystal X-ray diffraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(46 citation statements)
references
References 10 publications
0
46
0
Order By: Relevance
“…Recently, some examples for new kinds of topochemical and solid-state polymerizations have been reported. [153][154][155][156][157][158][159][160] Polymer syntheses in the solid state will become more important in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, some examples for new kinds of topochemical and solid-state polymerizations have been reported. [153][154][155][156][157][158][159][160] Polymer syntheses in the solid state will become more important in the future.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, several examples are known in which the repeating arrangements of the monomers harmonize with the resulting polymer unit to keep single crystals even after the polymerization. The classical examples are the topochemical polymerization of distyrylpyrazines17–19 and diacetylenes,20 and some current examples are dienes,21–23 trienes,24 and quinodimethanes 25, 26. It is thought that the combined design of a host cavity and a monomer arrangement may yield new stereoregular polymers.…”
Section: Resultsmentioning
confidence: 99%
“…If the trienes also are aligned with a tilt angle of about 29°, the reacting carbon atoms (C1-C6) of adjacent p-systems will approach each other to within a close contact (3.5 Å). Since these supramolecular structural features are very similar to those previously used for the triacetylene polymerization, Lauher and Fowler et al decided again to explore the same strategy for a 1,6-triene polymerization [67]. This approach involves the use of two molecules; one acts as the host, controlling the supramolecular structure and establishing the 7.2 Å translational repeat distance, and the other, the guest, is the intended triene monomer.…”
Section: Topochemical Polymerization Of Other Monomersmentioning
confidence: 94%
“…One of the intended triene guest molecules, shown in Scheme 10, was prepared and its crystal structure revealed a supramolecular structure that might Scheme 10 Topochemical 1,6-polymerization of a triene [67] be suitable for a topochemical polymerization. When the single crystal was heated to 110°C for 8 h, this process resulted in a smooth transformation to a new material whose X-ray crystal structure clearly demonstrated that a topochemical 1,6-polymerization of the triene to a polytriene had occurred.Although the polymerization of the triene was a serendipitous discovery, it clearly demonstrates that the topochemical polymerization of a triene is possible, thus adding it to the small but growing number of important topochemical reactions.…”
Section: Topochemical Polymerization Of Other Monomersmentioning
confidence: 99%